2016
DOI: 10.1111/aor.12838
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity in the Presentation of Decellularized Tissue Composition: The Need for Standardized Approaches

Abstract: Decellularization offers great potential to the field of tissue engineering, as this method gives rise to scaffold material with the native organ architecture by removing all cellular material and leaving much of the extracellular matrix (ECM) intact. However, many parameters may affect decellularization efficacy and ECM retention and, therefore, decellularization protocols need to be optimized for specific needs. This requires robust methods for comparison of decellularized tissue composition. Various represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Liver cirrhosis is accompanied by abnormal changes in ECM structure and composition (Klaas et al, ), remodeling in the ECM composition may alter cell signaling and facilitate liver regeneration for liver diseases (Klaas et al, ; Williams, Clouston, & Forbes, ). On the other hand, the decellularization procedure without using harsh detergents may result in structural integrity of ECM (Maghsoudlou et al, ); moreover, Triton X‐100, a mild detergent and typically used for liver decellularization (Badylak, Taylor, & Uygun, ), can only reduce cell component/DNA content without depleting any glycosaminoglycans (GAGs) during the washing process (Bruyneel & Carr, ). The effect could be attributed that GAGs and other components (collagen, proteoglycans) constitute the liver extracellular microenvironment, and also play an important role in hepatic functions and viability (Damania et al, ; Lee et al, ); furthermore, the wound ECM of GaIN‐damaged cells can be subsequently replaced by mature ECM and return to the preinjury state (Jonker, Dijkhuis, Boes, Hardonk, & Grond, ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis is accompanied by abnormal changes in ECM structure and composition (Klaas et al, ), remodeling in the ECM composition may alter cell signaling and facilitate liver regeneration for liver diseases (Klaas et al, ; Williams, Clouston, & Forbes, ). On the other hand, the decellularization procedure without using harsh detergents may result in structural integrity of ECM (Maghsoudlou et al, ); moreover, Triton X‐100, a mild detergent and typically used for liver decellularization (Badylak, Taylor, & Uygun, ), can only reduce cell component/DNA content without depleting any glycosaminoglycans (GAGs) during the washing process (Bruyneel & Carr, ). The effect could be attributed that GAGs and other components (collagen, proteoglycans) constitute the liver extracellular microenvironment, and also play an important role in hepatic functions and viability (Damania et al, ; Lee et al, ); furthermore, the wound ECM of GaIN‐damaged cells can be subsequently replaced by mature ECM and return to the preinjury state (Jonker, Dijkhuis, Boes, Hardonk, & Grond, ).…”
Section: Discussionmentioning
confidence: 99%
“…Decellularization refers to the process of treating a tissue with any combination of physical stress and chemical/enzymatic agents to remove cellular components, leaving behind only the noncellular ECM that can be used for therapeutic applications. The specific method of decellularization used depends on the tissue type; for instance, while cartilage tissue is able to undergo a relatively harsh treatment, lung tissue requires a more sensitive decellularization method to preserve its tissue composition . The resulting decellularized extracellular matrix (dECM) can then be processed further for different tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…The specific method of decellularization used depends on the tissue type; for instance, while cartilage tissue is able to undergo a relatively harsh treatment, lung tissue requires a more sensitive decellularization method to preserve its tissue composition. 14 The resulting decellularized extracellular matrix (dECM) can then be processed further for different tissue engineering applications. These applications are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…ANOVA test showed that no significant differences were evidenced in the tested protocols. It has been reported that a lower concentration of <50 ng/mg in a membrane implies that the matrix can be considered as decellularized [32,56]. Therefore, the chemical and mechanical methods used were effective at eliminating the DNA content from the DM.…”
Section: Decellularization Of Bam and Dna Contentmentioning
confidence: 99%